Political motives in climate and energy policy - Annegrete Bruvoll; Hanne Marit Dalen; Bodil M.Larsen (Statistics Norway, Research Department, 2012)
Standard economic theory provides clear guidance on the design of cost-efficient policy in the presence of imperfect markets and externalities. However, observed policies reveal extensive discrepancies between principles and practise. Based on interviews with core politicians from the Norwegian parliament, we investigate causes for the lack of cost efficiency in climate and energy policy. We find that politicians agree with the notion of cost efficiency in principle, but rather than ascribing efficient instruments directed at specific policy goals, they include concerns for industrial and regional development, income distribution and employment in the environmental policy design. Lacking insight in the functioning of economic instruments and perceptions of a non-binding budget constraint also violate the requirements for efficient policy decisions. The findings point to the role of economists and social scientists to communicate the functioning of complex instruments. Improved compensation procedures could help reduce the politicians' incentives to undermine efficiency in order to avoid unwanted distributional effects.
Keywords: Q48; Q54; Q58; 330; policy instruments; policy formulation; political processes; climate policy frameworks; energy policy